Rancang Bangun Aplikasi Persediaan Kayu pada PT Perkebunan Nusantara XII Surabaya - Bramanta, Tri Kunto Arif Bagus; Wibowo, Januar; Rahmawati, Endra (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
The availability of wood at PT Perkebunan Nusantara XII still awake. This is because the PTPN XII did not knowdetails of production and uses on time of wood on each garden. Unavailability of wood will have an impact on sales process wood in PTPN XII. In addition, the PTPN XII does not have production data and the most recent usage data wood carried on each other garden. The impact, inconsistency of data production and use of wood is often found between the gardens and PTPN XII, this will lead to staffing difficulties in knowing the stock of wood in a garden Applications built wood supplies to overcome the problems that exist in PTPN XII, and is built on the theory of supply. These web-based application built order office supplies directors may determine. the use and production of wood in every garden with ease. That applications have passed the test and got 100% results. Results obtained from these applications, will help the PTPN XII to know the wood supply in real time on the garden, and reduce the risk of delays in the receipt of inventory data in each garden, and could have an impact on earnings PTPN XIIKeyword: Aplication, Avaibility Wood, Stock